If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(w+2)(2w-1)=(w-2)(w-5)+15
We move all terms to the left:
(w+2)(2w-1)-((w-2)(w-5)+15)=0
We multiply parentheses ..
(+2w^2-1w+4w-2)-((w-2)(w-5)+15)=0
We calculate terms in parentheses: -((w-2)(w-5)+15), so:We get rid of parentheses
(w-2)(w-5)+15
We multiply parentheses ..
(+w^2-5w-2w+10)+15
We get rid of parentheses
w^2-5w-2w+10+15
We add all the numbers together, and all the variables
w^2-7w+25
Back to the equation:
-(w^2-7w+25)
2w^2-w^2-1w+4w+7w-2-25=0
We add all the numbers together, and all the variables
w^2+10w-27=0
a = 1; b = 10; c = -27;
Δ = b2-4ac
Δ = 102-4·1·(-27)
Δ = 208
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{208}=\sqrt{16*13}=\sqrt{16}*\sqrt{13}=4\sqrt{13}$$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-4\sqrt{13}}{2*1}=\frac{-10-4\sqrt{13}}{2} $$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+4\sqrt{13}}{2*1}=\frac{-10+4\sqrt{13}}{2} $
| 2/3=a-2/9 | | 13x-15=8+2x | | -4y+4=(-2(3y+2) | | 26=(-8/5)y | | 6x+15+43=8x-1 | | (3x+24)=7x | | b/6-10=-12 | | 2n+3-n=17 | | X/6-x/3=4 | | x+2-1/3=3/4 | | 10x+13x-33=180 | | k/12-3=0 | | 3x+178=180 | | k/12-1=0 | | 3(6n-1)=11n-45 | | x+-1/3=3/4 | | 3x+178+6x+238=180 | | -8+n/3=-5 | | x+2x=267 | | -7-5r=-6r | | -10x-11x+38=-1x+40 | | 5x+33+14=7x-10 | | 7/x*9=21/36 | | 7n+23}+5n=59 | | 8-(h-2)(h+7)=(2+h)(4+h) | | 0=w-4 | | 7+3k-12k=3k+1 | | 3.50+31x=294 | | -4+n/4=-6 | | 5d-2-3d=18/2*3-20 | | 3k-12k=3k+1 | | 15+x/8=2+4 |